2011
DOI: 10.5658/wood.2011.39.5.451
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Rapeseed Flour-based Wood Adhesives for Making Wood Flooring

Abstract: Adhesives derived from renewable resources allow wood panel producers to make lower cost alternatives to formaldehyde-based adhesive resins. Among them, adhesive components extracted from industrial by-products or wastes are the most important research fields in the efficient utilization of waste and cost reduction. In our study, the rapeseed flour, which is a by product from the production of biodiesel extracted from rapeseed, was introduced to develop alternative adhesives for the production of wood flooring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…RF was first hydrolyzed with NaOH, mixed with PF resin at molar ratios of 1.8, 2.1, and 2.4 (RF/PF), applied to plywood veneer at a loading level of 300 g/m 2 , and cured at 140 °C and 10 kg/cm 2 for 5 min. The resulting plywood showed acceptable average density, moisture content, formaldehyde emission, and critical stress as specified in Korean Standards at higher RF/PF ratios (Yang et al, ). Further research on blending with different synthetic resins and different concentrations would be helpful in formulating effective blended adhesives from CP.…”
Section: Canola Protein As An Alternate Source For Protein‐based Adhementioning
confidence: 96%
See 2 more Smart Citations
“…RF was first hydrolyzed with NaOH, mixed with PF resin at molar ratios of 1.8, 2.1, and 2.4 (RF/PF), applied to plywood veneer at a loading level of 300 g/m 2 , and cured at 140 °C and 10 kg/cm 2 for 5 min. The resulting plywood showed acceptable average density, moisture content, formaldehyde emission, and critical stress as specified in Korean Standards at higher RF/PF ratios (Yang et al, ). Further research on blending with different synthetic resins and different concentrations would be helpful in formulating effective blended adhesives from CP.…”
Section: Canola Protein As An Alternate Source For Protein‐based Adhementioning
confidence: 96%
“…Several research groups have explored the potential of protein modifications in order to improve the adhesive performance of CP‐based adhesives. Among them, denaturation (Li, Qi, Sun, et al, ; Li, Qi, Sun, & Wang, ), chemical modification (Bandara & Wu, ; Hale, ; Li, Qi, Sun, et al, ; Wang et al, ), cross‐linking (Hale, ; Wang et al, ), blending with synthetic resins (Yang, Ahn, Choi, & Han, ), and exfoliating nanomaterials (Bandara et al, ; Bandara et al, ; Bandara & Wu, ) have shown success for CP to different degrees in improving their adhesion properties.…”
Section: Canola Protein As An Alternate Source For Protein‐based Adhementioning
confidence: 99%
See 1 more Smart Citation